INTERDEPENDENCE OF OIL PRICE VOLATILITY AND RUBLE EXCHANGE RATE DURING THE CRISIS IN UKRAINE - Balaban, Suzana; Pavićević, Vladimir; Simić, Milica (Oditor, 2024)
The subject of research in this paper is the impact of the crisis in Ukraine on the volatility of the ruble and oil, as well as the correlation of these values with each other. In order to investigate the impact of the crisis in Ukraine as an external shock on the volatility of the ruble and crude oil, changes in the ratio of their values were analyzed on a daily basis, in the observed period during 2022 and the first four months of 2023. The analysis of time series, and then the comparative analysis of the mentioned data and the use of the GARCH model determined a certain divergence in the very nature of the behavior and movement of the ruble and oil immediately before the beginning and during the crisis in Ukraine, during the observed period. There is no doubt that the Russian currency and crude oil markets behaved much more volatile in this period, which implies a significantly greater impact on economic activities, bearing in mind the instability of the value of the ruble and oil as significant factors affecting the overall economic trends in the world. Predmet istraživanja ovog rada je uticaj krize u Ukrajini na volatilnost rublje i nafte, kao i korelacija ovih vrednosti međusobno. Kako bi istražili uticaj krize u Ukrajini, kao eksternog šoka na volatilnost rublje i sirove nafte analizirane su promene odnosa njihovih vrednosti na dnevnom nivou, u posmatranom periodu tokom 2022. godine i prva četiri meseca 2023. godine. Analizom vremenskih serija, a potom i komparativnom analizom navednih podataka i korišćenjem GARCH modela utvrđena je određena divergentnost u samoj prirodi ponašanja i kretanja rublje i nafte neposredno pre početka i tokom trajanja krize u Ukrajini, u toku posmatranog perioda. Nema sumnje da su se tržišta ruske valute i sirove nafte u ovom periodu ponašala mnogo volatilnije, što implicira i značajno veći uticaj na ekonomske aktivnosti, imajući u vidu nestabilnost vrednosti rublje i nafte kao značajnih činilaca uticaja na ukupna ekonomska kretanja u svetu.